Drosophila CPEB Orb2A Mediates Memory Independent of Its RNA-Binding Domain - Krüttner, Sebastian (Cell Press, 2012)
Long-term memory and synaptic plasticity are thought to require the synthesis of new proteins at activated synapses. The CPEB family of RNA binding proteins, including Drosophila Orb2, has been implicated in this process. The precise mechanism by which these molecules regulate memory formation is however poorly understood. We used gene targeting and site-specific transgenesis to specifically modify the endogenous orb2 gene in order to investigate its role in long-term memory formation. We show that the Orb2A and Orb2B isoforms, while both essential, have distinct functions in memory formation. These two isoforms have common glutamine-rich and RNA-binding domains, yet Orb2A uniquely requires the former and Orb2B the latter. We further show that Orb2A induces Orb2 complexes in a manner dependent upon both its glutamine-rich region and neuronal activity. We propose that Orb2B acts as a conventional CPEB to regulate transport and/or translation of specific mRNAs, whereas Orb2A acts in an unconventional manner to form stable Orb2 complexes that are essential for memory to persist.